Potato Disease Prevalence and Quality Performance Under Four Soil Health-Related Practices - Kate Binzen Fuller; Kusum Adhikari; Alexander Maas; Christopher McIntosh; Carl Rosen; James E. Crants; Robert P. Larkin; Kim Zitnick Anderson; Anna Stasko; Julie Pasche; Kenneth Frost; Jeff Miller; et al. (American Journal of Potato Research, 2026)

AI-driven analysis of cattle behaviour in lairage: Impact of flooring substrate and implications for welfare and management - Dana L.M. Campbell; Qiyu Liao; Caroline Lee; Shenghong Li; Muhammad Rizwan Khokher; Xin Yuan; Stuart Anderson; Jingyu Zhang; Xinlong Guan; Troy Kalinowski; Neil Bagnall; Dadong Wang (Applied Animal Behaviour Science, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Progress, challenges and future directions in marine organic-walled dinoflagellate cyst research: New insights from an international workshop - Iria García-Moreiras; Ana Amorim; Vera Pospelova; Karin Zonneveld; Donald M. Anderson; Girish Beedessee; Amy Dale; Barrie Dale; Ophélie David; Anne de Vernal; Eugenia Fatourou; Emilie Folie-Boivin; et al. (Marine Micropaleontology, 2025)

First insights into the fine-scale vertical movements of a Carolina hammerhead, Sphyrna gilberti, and a hybrid between Carolina and scalloped hammerhead - Lauren Horstmyer; Kirsty Ballard; Toby Daly-Engel; Kieran Stein; Eric Hoffmayer; Neil Hammerschlag; Bryan S. Frazier; Brooke Anderson; Beckah Campbell; James Sulikowski (Frontiers in Marine Science, 2025)
Satellite telemetry has enabled the tracking of marine predators’ vertical and horizontal habitat use and migration patterns. These insights provide valuable information that inform management and conservation of threatened species. In this study, a scalloped hammerhead, Sphyrna lewini, (125 cm FL; immature female) a Carolina hammerhead, Sphyrna gilberti, (138 cm FL; immature female) and a scalloped/Carolina hammerhead hybrid (160 cm FL; immature male) were tagged with PSATLIFE’s off the coast of North Carolina. Tag data revealed that the Carolina hammerhead exploited a wide depth range, with a maximum depth of 846 m. Dive patterns of the scalloped hammerhead revealed differences in vertical space use, with the scalloped hammerhead primarily remaining within the top 200 m of the water column, and with a maximum depth of 380 m. The hybrid individual demonstrated similar dive patterns to those of the scalloped hammerhead, with a maximum depth of 203 m. This study presents the first vertical movement data for Carolina and hybrid scalloped/Carolina hammerheads, offering new insights into interspecific variation in depth use. Future research should explore if there are differences in habitat use and foraging strategies, as they may serve as distinguishing characteristics and support the development of effective management measures.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Barriers to family planning for female surgery residents - breastfeeding - Briana Griffin; Terry Gordon; Ariel Vinson; Ja'Neil Humphrey; Bryce Gantt; Oliver Alexander; Chilando Mulenga; Andrianna Anderson; Kylar Wiltz; Mauricio Downer (Next Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Life stage and seasonal habitat use of the porbeagle Lamna nasus in the Northwest Atlantic Ocean - Brooke N. Anderson; Neil Hammerschlag; Steven Saul; Jon F. Dodd; Heather D. Bowlby; Yun Kang; Austin J. Gallagher; James A. Sulikowski (Frontiers in Marine Science, 2025)
For highly mobile marine species such as pelagic elasmobranchs, the development of effective spatial management requires a comprehensive understanding of movement ecology. Research incorporating movement data across seasons and life stages, including reproductive states, is valuable for informing spatial management, yet is absent for most species. In the Northwest (NW) Atlantic Ocean (hereafter referred to as NW Atlantic), the porbeagle shark Lamna nasus is a pelagic species that is overfished, has a live retention ban (Canada) or landings regulations (United States), and is also commonly captured incidentally as bycatch. Research on the spatiotemporal dynamics of NW Atlantic porbeagle habitat use is limited, with all previous research utilizing pop-off satellite archival tags that are prone to large uncertainty in location estimates. This study used higher-accuracy fin-mount satellite tags to identify patterns in habitat use across life stages and seasons for porbeagle sharks tagged off the northeastern coast of the United States. During the summer and fall, the 95% kernel density estimate (referred to as “activity space”) of tagged porbeagles occurred almost exclusively on the continental shelf in the Gulf of Maine and Georges Bank. Activity space expanded and shifted southwards to include offshore environments during the winter and spring for juveniles, mature non-gravid females, and mature females of unknown reproductive states, while the activity space of mature males and gravid females remained in shelf waters year-round. This finding differs from the previous assumption that southward migrations are linked to reproduction for NW Atlantic porbeagles. Tagged porbeagles were also found to have a relatively small 50% kernel density estimate (referred to as “high occupancy area”) located around Cape Cod, Massachusetts that was well-conserved across life stages and seasons. This relatively static, small high occupancy area has implications for the population’s conservation given the high amount of fishing activity (rod-and-reel, trawl, gillnet) occurring within this region. Given the overlap between porbeagle high occupancy area and fishing activity, as well as the relatively high recapture rate of tagged sharks (10.5%), the coastal waters around Cape Cod, Massachusetts should be considered for spatial management of the NW Atlantic porbeagle.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Drought susceptibility mapping in Iraq using GRACE/GRACE-FO, GLDAS, and machine learning algorithms - Alaa M. Al-Abadi; Ayat Ali Hassan; Noor M. Al-Moosawi; Amna M. Handhal; Hassan Alzahrani; Fadhil K. Jabbar; Neil L. Anderson (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

The socioeconomic impact of equine epizootic lymphangitis in working equids in low and middle-income countries: A scoping review - Marta Bonsi; Neil Euan Anderson; Gemma Carder (Journal of Equine Veterinary Science, 2024)

Distinct patterns of inheritance shape life‐history traits in steelhead trout - Anne K. Beulke; Alicia Abadía‐Cardoso; Devon E. Pearse; Laura C. Goetz; Neil F. Thompson; Eric C. Anderson; John Carlos Garza (Molecular Ecology, 2023)
Life‐history variation is the raw material of adaptation, and understanding its genetic and environmental underpinnings is key to designing effective conservation strategies. We used large‐scale genetic pedigree reconstruction of anadromous steelhead trout ( Oncorhynchus mykiss ) from the Russian River, CA, USA, to elucidate sex‐specific patterns of life‐history traits and their heritability. SNP data from adults returning from sea over a 14‐year period were used to identify 13,474 parent–offspring trios. These pedigrees were used to determine age structure, size distributions and family sizes for these fish, as well as to estimate the heritability of two key life‐history traits, spawn date and age at maturity (first reproduction). Spawn date was highly heritable ( h 2 = 0.73) and had a cross‐sex genetic correlation near unity. We provide the first estimate of heritability for age at maturity in ocean‐going fish from this species and found it to be highly heritable ( h 2 from 0.29 to 0.62, depending on sex and method), with a much lower genetic correlation across sexes. We also evaluated genotypes at a migration‐associated inversion polymorphism and found sex‐specific correlations with age at maturity. The significant heritability of these two key reproductive traits in these imperiled fish, and their patterns of inheritance in the two sexes, is consistent with predictions of both natural and sexually antagonistic selection (sexes experience opposing selection pressures). This emphasizes the importance of anthropogenic factors, including hatchery practices and ecosystem modifications, in shaping the fitness of this species, thus providing important guidance for management and conservation efforts.

Sea level rise adaptation pushes an insular endemic rodent closer to extinction - Paul J. Taillie; Sandra Sneckenberger; Neil Perry; Chad Anderson; Kevin Kalasz; Robert A. McCleery (Biodiversity and Conservation, 2023)
Understanding how species will respond to a rapidly changing global climate is requisite to conserving biodiversity. Though habitat losses from human development and land use change remain the most critical threats to biodiversity globally, some regions, such as low-lying islands, are particularly vulnerable to the effects of climate change. Despite this vulnerability, there may be opportunities for imperiled species on islands to adapt to the effects of climate-induced sea level rise. To understand how the response to rising seas may influence the amount of future habitat, we investigated shifts in the elevational range of the endangered silver rice rat ( Oryzomys palustris natator; hereafter “rice rat”), a species endemic to tidal environments of the Lower Florida Keys, USA. We quantified fine-scale habitat use using radio telemetry of collared animals, first in 2004, and again in 2021, thus spanning a 17-year period during which the local sea level rose by 0.142 m. We observed a shift in the elevational range limits of rice rats which closely mirrored the rise in sea level, and that this apparent ability to adapt to rising sea level decreased the extent of habitat loss in subsequent decades. However, over longer time scales (~ 100 yrs), the extent of habitat loss from sea level rise outpaced rice rats’ ability to adapt. As such, the conservation of biodiversity on low-lying islands hinges on the ability of the global community to decrease anthropogenic greenhouse gas emissions and mitigate the associated consequences for the global climate. Otherwise, conservation practitioners will be increasingly forced to make difficult decisions about how to conserve imperiled species on low-lying islands.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Cerebrospinal fluid levels of 5-HIAA and dopamine in people with HIV and depression - Rong Fu; Hyder Jinnah; J. Lucas Mckay; Andrew H. Miller; Jennifer C. Felger; Eugene W. Farber; Sanjay Sharma; Neil Whicker; Raeanne C. Moore; Donald Franklin; Scott L. Letendre; Albert M. Anderson (Journal of NeuroVirology, 2023)

The impact of COVID-19 public health restrictions on particulate matter pollution measured by a validated low-cost sensor network in Oxford, UK - Tony Bush; Suzanne Bartington; Francis D. Pope; Ajit Singh; G. Neil Thomas; Brian Stacey; George Economides; Ruth Anderson; Stuart Cole; Pedro Abreu; Felix C.P. Leach (Building and Environment, 2023)

Geophysical site assessment of soil and the rock structure in karst terrain using 2D and 3D mapping of noninvasive electrical resistivity tomography—southwestern of MO, USA - Diya Alfuqara; Neil Anderson (Arabian Journal of Geosciences, 2023)

Habitat restoration weakens negative environmental effects on telomere dynamics - Darryl McLennan; Sonya K. Auer; Simon McKelvey; Lynn McKelvey; Graeme Anderson; Winnie Boner; Jessica S. Duprez; Neil B. Metcalfe (Molecular Ecology, 2022)
Habitat quality can have far‐reaching effects on organismal fitness, an issue of concern given the current scale of habitat degradation. Many temperate upland streams have reduced nutrient levels due to human activity. Nutrient restoration confers benefits in terms of invertebrate food availability and subsequent fish growth rates. Here we test whether these mitigation measures also affect the rate of cellular ageing of the fish, measured in terms of the telomeres that cap the ends of eukaryotic chromosomes. We equally distributed Atlantic salmon eggs from the same 30 focal families into 10 human‐impacted oligotrophic streams in northern Scotland. Nutrient levels in five of the streams were restored by simulating the deposition of a small number of adult Atlantic salmon Salmo salar carcasses at the end of the spawning period, while five reference streams were left as controls. Telomere lengths and expression of the telomerase reverse transcriptase (TERT) gene that may act to lengthen telomeres were then measured in the young fish when 15 months old. While TERT expression was unrelated to any of the measured variables, telomere lengths were shorter in salmon living at higher densities and in areas with a lower availability of the preferred substrate (cobbles and boulders). However, the adverse effects of these habitat features were much reduced in the streams receiving nutrients. These results suggest that adverse environmental pressures are weakened when nutrients are restored, presumably because the resulting increase in food supply reduces levels of both competition and stress.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Observations of a species‐record deep dive by a central Pacific female scalloped hammerhead shark ( Sphyrna lewini ) - James M. Anderson; Patrick T. Rex; Kelsey Maloney; Mark Johnston; Deron Verbeck; Neil Allen; Kim Holland (Journal of Fish Biology, 2022)
A female scalloped hammerhead shark ( Sphyrna lewini ) conducted a species record deep dive to 1240 m in coastal‐pelagic waters off Hawaii Island. This extends the deepest known depth range of the species by over 200 m (650 ft) and highlights the question of the extent to which deep‐diving activity is mediated by physiological constraints, such as temperature and oxygen availability.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Applying Mendelian randomization to appraise causality in relationships between nutrition and cancer - Kaitlin H. Wade; James Yarmolinsky; Edward Giovannucci; Sarah J. Lewis; Iona Y. Millwood; Marcus R. Munafò; Fleur Meddens; Kimberley Burrows; Joshua A. Bell; Neil M. Davies; Daniela Mariosa; Noora Kanerva; et al. (Cancer Causes & Control, 2022)
Dietary factors are assumed to play an important role in cancer risk, apparent in consensus recommendations for cancer prevention that promote nutritional changes. However, the evidence in this field has been generated predominantly through observational studies, which may result in biased effect estimates because of confounding, exposure misclassification, and reverse causality. With major geographical differences and rapid changes in cancer incidence over time, it is crucial to establish which of the observational associations reflect causality and to identify novel risk factors as these may be modified to prevent the onset of cancer and reduce its progression. Mendelian randomization (MR) uses the special properties of germline genetic variation to strengthen causal inference regarding potentially modifiable exposures and disease risk. MR can be implemented through instrumental variable (IV) analysis and, when robustly performed, is generally less prone to confounding, reverse causation and measurement error than conventional observational methods and has different sources of bias (discussed in detail below). It is increasingly used to facilitate causal inference in epidemiology and provides an opportunity to explore the effects of nutritional exposures on cancer incidence and progression in a cost-effective and timely manner. Here, we introduce the concept of MR and discuss its current application in understanding the impact of nutritional factors (e.g., any measure of diet and nutritional intake, circulating biomarkers, patterns, preference or behaviour) on cancer aetiology and, thus, opportunities for MR to contribute to the development of nutritional recommendations and policies for cancer prevention. We provide applied examples of MR studies examining the role of nutritional factors in cancer to illustrate how this method can be used to help prioritise or deprioritise the evaluation of specific nutritional factors as intervention targets in randomised controlled trials. We describe possible biases when using MR, and methodological developments aimed at investigating and potentially overcoming these biases when present. Lastly, we consider the use of MR in identifying causally relevant nutritional risk factors for various cancers in different regions across the world, given notable geographical differences in some cancers. We also discuss how MR results could be translated into further research and policy. We conclude that findings from MR studies, which corroborate those from other well-conducted studies with different and orthogonal biases, are poised to substantially improve our understanding of nutritional influences on cancer. For such corroboration, there is a requirement for an interdisciplinary and collaborative approach to investigate risk factors for cancer incidence and progression.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Riparian populations of minnesota reed canarygrass (Phalaris arundinacea) are most likely native, based on SNPs (DArTseqLD) - Andrzej K. Noyszewski; Neil O. Anderson; Alan G. Smith; Andrzej Kilian; Diana Dalbotten; Emi Ito; Anne Timm; Holly Pellerin; Barbora Kubátová; Tereza Kávová; Vojtěch Januš; Vladislav Čurn; et al. (Wetlands Ecology and Management, 2021)
The native vs. exotic status of reed canarygrass (RCG), a major invasive species of Minnesota wetlands, is unknown. The aim of this study was to investigate this native vs. exotic status to enhance its management. Genetic comparison of wild RCG populations from six Minnesota and six Czech Republic rivers was performed. A total of 2521 polymorphic SNP markers (single nucleotide polymorphisms) were used to evaluate 478 RCG samples across all collections. In the PCoA, all (n = 256) tested extant wild, riparian RCG genotypes from six Minnesota Rivers and six Czech Republic Rivers were genetically distinct, although some SNPs were common in both populations since they are the same species. DAPC analysis also resulted in the formation of two primary clusters separating the Minnesota Rivers and Czech Republic Rivers riparian samples, with little overlap; STRUCTURE analysis also supported this clustering with k = 4 groups as it separated the Czech Republic Rivers populations into three groups, along with Minnesota Rivers. The uniformity of PCoA, DAPC, STRUCTURE, and Evanno results indicates the distinct separation of Minnesota Rivers and Czech Republic Rivers populations. Portions of the genome (specific SNPs) are preserved or in common across continents, as indicated by STRUCTURE similarities. Nonetheless, overall significant SNP differences between the continents indicate that the Minnesota riparian populations are distinct enough from the European (Czech) collections to be delineated as native N. American RCG. PCoA of all the Minnesota RCG collections clustered Minnesota Rivers, Herbarium, Extant Herbarium, Research Field and Native Field collections together. STRUCTURE analysis (k = 2; Evanno) divided these Minnesota collections from the Commercial Field and Cultivars collections. There are two genetically distinct groups of RCG in Minnesota and since the Minnesota Rivers, the Research Field, the Native Field and pre-1930 herbaria collections clustered together, they are most likely native N. American types. Analysis of molecular variance (AMOVA) indicated that the genetic variation was more significant within, rather than among, the RCG populations. Native, historic herbaria types cluster together with all wild RCG river populations in Minnesota, all of which were distinct from those in Central Europe, suggesting native RCG type persistence in N. America. Also, cultivated forage types of RCG are distinct from wild RCG Minnesota river populations. The SNP genetic data shows that riparian Minnesota RCG populations are native. These data will facilitate future management strategies to control RCG as a native, but invasive, species.

Condition Assessment of Building Foundation in Karst Terrain Using both Electrical Resistivity Tomography and Multi-channel Analysis Surface Wave Techniques - Yunsen Wang; Neil Anderson; Evgeniy Torgashov (Geotechnical and Geological Engineering, 2020)

Distribution of FMRFamide-related peptides and co-localization with glutamate in Cupiennius salei, an invertebrate model system - Emily A. Tarr; Brian M. Fidler; Kyrstin E. Gee; Carly M. Anderson; Anna K. Jager; Neil M. Gallagher; Kaelyn P. Carroll; Ruth Fabian-Fine (Cell and Tissue Research, 2019)

Impact of total laboratory automation on workflow and specimen processing time for culture of urine specimens - Melanie L. Yarbrough; William Lainhart; Allison R. McMullen; Neil W. Anderson; Carey-Ann D. Burnham (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Nutrients from salmon parents alter selection pressures on their offspring - Sonya K. Auer; Graeme J. Anderson; Simon McKelvey; Ronald D. Bassar; Darryl McLennan; John D. Armstrong; Keith H. Nislow; Helen K. Downie; Lynn McKelvey; Thomas A.J. Morgan; Karine Salin; Danielle L. Orrell; et al. (Ecology Letters, 2018)
Organisms can modify their surrounding environment, but whether these changes are large enough to feed back and alter their evolutionary trajectories is not well understood, particularly in wild populations. Here we show that nutrient pulses from decomposing Atlantic salmon ( Salmo salar ) parents alter selection pressures on their offspring with important consequences for their phenotypic and genetic diversity. We found a strong survival advantage to larger eggs and faster juvenile metabolic rates in streams lacking carcasses but not in streams containing this parental nutrient input. Differences in selection intensities led to significant phenotypic divergence in these two traits among stream types. Stronger selection in streams with low parental nutrient input also decreased the number of surviving families compared to streams with high parental nutrient levels. Observed effects of parent‐derived nutrients on selection pressures provide experimental evidence for key components of eco‐evolutionary feedbacks in wild populations.

Diffusion Tensor Tractography of the Cerebellar Peduncles in Prematurely Born 7-Year-Old Children - Eilon Shany; Terrie E. Inder; Sharon Goshen; Iris Lee; Jeffrey J. Neil; Christopher D. Smyser; Lex W. Doyle; Peter J. Anderson; Joshua S. Shimony (The Cerebellum, 2017)

Flexibility in metabolic rate and activity level determines individual variation in overwinter performance - Sonya K. Auer; Karine Salin; Graeme J. Anderson; Neil B. Metcalfe (Oecologia, 2016)

Estimating behavior in a black box: how coastal oceanographic dynamics influence yearling Chinook salmon marine growth and migration behaviors - Brian J. Burke; James J. Anderson; Jessica A. Miller; Londi Tomaro; David J. Teel; Neil S. Banas; António M. Baptista (Environmental Biology of Fishes, 2016)

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins - Przemyslaw Szafranski; Tomasz Gambin; Avinash V. Dharmadhikari; Kadir Caner Akdemir; Shalini N. Jhangiani; Jennifer Schuette; Nihal Godiwala; Svetlana A. Yatsenko; Jessica Sebastian; Suneeta Madan-Khetarpal; Urvashi Surti; Rosanna G. Abellar; et al. (Human Genetics, 2016)

Assessing the value of a marine world heritage site to the ecology and conservation of apex predatory sharks - Acuna Marrero David; Hearn Alex; Hammerschlag Neil; Calich Hannah; Anderson Marti; Pawley Matthew; Salinas De Leon Pelayo (Frontiers in Marine Science, 2016)

Variation Among Genotypes and Source Habitats in Growth and Fecundity of the Wetland Invasive Plant Phalaris arundinacea L - Michael F. Nelson; Neil O. Anderson (Wetlands, 2015)

Doubling of coastal erosion under rising sea level by mid-century in Hawaii - Tiffany R. Anderson; Charles H. Fletcher; Matthew M. Barbee; L. Neil Frazer; Bradley M. Romine (Natural Hazards, 2015)

Juvenile myelomonocytic leukemia due to a germline CBL Y371C mutation: 35-year follow-up of a large family - Anand Pathak; Alexander Pemov; Mary L. McMaster; Ramita Dewan; Sarangan Ravichandran; Evgenia Pak; Amalia Dutra; Hyo Jung Lee; Aurelie Vogt; Xijun Zhang; Meredith Yeager; Stacie Anderson; et al. (Human Genetics, 2015)

Modeling sea-level rise vulnerability of coastal environments using ranked management concerns - Haunani H. Kane; Charles H. Fletcher; L. Neil Frazer; Tiffany R. Anderson; Matthew M. Barbee (Climatic Change, 2015)

Mapping subvertical discontinuities in rock cuts using a 400-MHz ground penetrating radar antenna - Adnan Aqeel; Neil Anderson; Norbert Maerz (Arabian Journal of Geosciences, 2014)

Population genetic structure of N. American and European Phalaris arundinacea L. as inferred from inter-simple sequence repeat markers - Michael F. Nelson; Neil O. Anderson; Michael D. Casler; Andrew R. Jakubowski (Biological Invasions, 2014)

The transmitting tissue of Nicotiana tabacum is not essential to pollen tube growth, and its ablation can reverse prezygotic interspecific barriers - Alan G. Smith; Carrie A. Eberle; Nicole G. Moss; Neil O. Anderson; Benjamin M. Clasen; Adrian D. Hegeman (Plant Reproduction, 2013)

Local-level determinants of wildcat occupancy in Northeast Scotland - André P. Silva; Luís M. Rosalino; Paul J. Johnson; David W. Macdonald; Neil Anderson; Kerry Kilshaw (European Journal of Wildlife Research, 2013)

Archaeological exploration using magnetic and GPR methods at the first court of Hatshepsut Temple in Luxor, Egypt - Hatem Odah; Ahmed Ismail; Ibrahim Elhemaly; Neil Anderson; Abbas M. Abbas; Fathy Shaaban (Arabian Journal of Geosciences, 2013)

Detection and Differentiation of Potato Virus Y Strains from Potato Using Immunocapture Multiplex RT-PCR - Ipsita Mallik; Nolan R. Anderson; Neil C. Gudmestad (American Journal of Potato Research, 2012)

Use of morphological, molecular markers and cytology to differentiate between closely related Gaura coccinea, G. drummondii for breeding purposes - Grace M. Pietsch; Neil O. Anderson (Euphytica, 2012)

Neurometabolite Abnormalities in Simian Immunodeficiency Virus-Infected Macaques with Chronic Morphine Administration - Christine C. Cloak; Linda Chang; Shawn P. O’Neil; Thomas M. Ernst; Daniel C. Anderson; Robert M. Donahoe (Journal of Neuroimmune Pharmacology, 2011)

Competive ability of invasive Miscanthus biotypes with aggressive switchgrass - Mary Hockenberry Meyer; Joe Paul; Neil O. Anderson (Biological Invasions, 2010)

Erratum to: Conundrums of a complex vector for invasive species control: a detailed examination of the horticultural industry - Jennifer Drew; Neil Anderson; David Andow (Biological Invasions, 2010)

Conundrums of a complex vector for invasive species control: a detailed examination of the horticultural industry - Jennifer Drew; Neil Anderson; David Andow (Biological Invasions, 2010)

Wolverine gene flow across a narrow climatic niche - Michael K. Schwartz; Jeffrey P. Copeland; Neil J. Anderson; John R. Squires; Robert M. Inman; Kevin S. McKelvey; Kristy L. Pilgrim; Lisette P. Waits; Samuel A. Cushman (Ecology, 2009)
Wolverines ( Gulo gulo ) are one of the rarest carnivores in the contiguous United States. Effective population sizes in Montana, Idaho, and Wyoming, where most of the wolverines in the contiguous United States exist, were calculated to be 35 (credible limits, 28–52) suggesting low abundance. Landscape features that influence wolverine population substructure and gene flow are largely unknown. Recent work has identified strong associations between areas with persistent spring snow and wolverine presence and range. We tested whether a dispersal model in which wolverines prefer to disperse through areas characterized by persistent spring snow cover produced least‐cost paths among all individuals that correlated with genetic distance among individuals. Models simulating large preferences for dispersing within areas characterized by persistent spring snow explained the data better than a model based on Euclidean distance. Partial Mantel tests separating Euclidean distance from spring snow‐cover‐based effects indicated that Euclidean distance was not significant in describing patterns of genetic distance. Because these models indicated that successful dispersal paths followed areas characterized by spring snow cover, we used these understandings to derive empirically based least‐cost corridor maps in the U.S. Rocky Mountains. These corridor maps largely explain previously published population subdivision patterns based on mitochondrial DNA and indicate that natural colonization of the southern Rocky Mountains by wolverines will be difficult but not impossible.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Epigenetic variation in tissue cultured Gaura lindheimeri - Grace M. Pietsch; Neil O. Anderson (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Statistical discrimination between pollen tube growth and seed set in establishing self incompatibility in Gaura lindheimeri 1 - William L. Peters; Neil O. Anderson (Euphytica, 2006)

Foreword - Neil Anderson; Susan Galatowitsch (Euphytica, 2006)

Minnesota horticultural industry survey on invasive plants - William L. Peters; Mary Hockenberry Meyer; Neil O. Anderson (Euphytica, 2006)

Trifluralin-mediated polyploidization of Rosa chinensis minima (Sims) Voss seedlings - David C. Zlesak; Christian A. Thill; Neil O. Anderson (Euphytica, 2005)

Freshwater to seawater acclimation of juvenile bull sharks (Carcharhinus leucas): plasma osmolytes and Na+/K+-ATPase activity in gill, rectal gland, kidney and intestine - Richard D. Pillans; Jonathan P. Good; W. Gary Anderson; Neil Hazon; Craig E. Franklin (Journal of Comparative Physiology B, 2005)

New Zealand Demersal Fish Assemblages - Malcolm P. Francis; Rosemary J. Hurst; Brian H. McArdle; Neil W. Bagley; Owen F. Anderson (Environmental Biology of Fishes, 2002)

Invasiveness in wetland plants in temperate North America - Susan M. Galatowitsch; Neil O. Anderson; Peter D. Ascher (Wetlands, 1999)

Distribution and population dynamics of Porphyra (Bangiales, Rhodophyta) in the southern Western Cape, South Africa - Neil J. Griffin; John J. Bolton; Robert J. Anderson (Journal of Applied Phycology, 1999)

A seismic study of salt dissolution in the Stettler area south-central Alberta, Canada - Neil L. Anderson; Ronald C. Hinds (Carbonates and Evaporites, 1997)

Glacial loading and unloading: a possible cause of rock salt dissolution in the Western Canada Basin - Neil L. Anderson; Ronald C. Hinds (Carbonates and Evaporites, 1997)

Early detection of Verticillium wilt resistance in a potato breeding program - German P. Hoyos; Florian I. Lauer; Neil A. Anderson (American Journal of Potato Research, 1993)

The Potato Association of America 75th Annual Meeting Spokane, Washington, U.S.A. - David Curwen; Pete Weingartner; Ronald Knight; Therese M. Work; Hugh J. Murphy; Steven B. Johnson; Richard Zink; Leigh Morrow; A. R. Mosley; Rod Davidson; Thoms Owings; Don Halseth; et al. (American Journal of Potato Research, 1991)

An assay to quantify vascular colonization of potato byVerticillium dahliae - German P. Hoyos; Paul J. Zambino; Neil A. Anderson (American Journal of Potato Research, 1991)